Diseño de máquina trituradora de desechos de Drywall con capacidad de 6 toneladas/día para la empresa 2SG Soluciones Ambientales S.A.S (2023)
This document develops the design of a drywall sheet shredding machine, as an alternative for the company 2SG Soluciones Ambientales S.A.S., for the reduction of drywall waste, coming from constructions and remodeling. The project begins with the analysis of the drywall sheet, the types of recycling of this material, the study of the parameters required in the crushing process is carried out.